1996
DOI: 10.1002/jmri.1880060622
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the female pelvic floor in the supine and upright positions

Abstract: The goal of this study was to determine whether a .5-T open configuration magnet system could be used to evaluate the female pelvic floor support structures and their functional changes in the upright and supine positions. We evaluated five normal volunteers with full bladders in the supine and sitting positions. Multiple measurements were obtained, including distance between symphysis and urethra, bladder neck to fixed pubococcygeal line, and posterior urethrovesical angle. The pelvic floor was evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Strengths of our methods include the use of a custom-designed computer-controlled servoactuator device able to make highly accurate force-displacement measurements, as well as the use of well-developed MRI strategies for quantifying physiological movements. It would be ideal to perform these studies in the standing posture, but at the present time, this has not been feasible, and comparison of upright and supine images of the pelvic floor do not show major differences [15]. Additionally, our technique using dynamic stress MRI to assess physiologic uterine movement allows for precise imaging and measurement of uterine location without instrumentation of the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of our methods include the use of a custom-designed computer-controlled servoactuator device able to make highly accurate force-displacement measurements, as well as the use of well-developed MRI strategies for quantifying physiological movements. It would be ideal to perform these studies in the standing posture, but at the present time, this has not been feasible, and comparison of upright and supine images of the pelvic floor do not show major differences [15]. Additionally, our technique using dynamic stress MRI to assess physiologic uterine movement allows for precise imaging and measurement of uterine location without instrumentation of the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when attempting to prevent urine leakage the PFMs should presumably have to work harder in sitting and standing, anti-gravity positions, than in supine, a gravity eliminated position. Magnetic resonance imaging evidence by Fielding et al indicated that in five continent women the angles between the urethra and the bladder base were the same in supine and standing but greater in sitting (Fielding et al, 1996). An increase in the angle between the bladder base and the urethra is seen during micturition (DeLancey, 1990), and a larger resting angle induced posturally or otherwise may therefore contribute to leakage in women with SUI.…”
Section: Introductionmentioning
confidence: 96%
“…Comparative studies of anatomic preparations and healthy subjects yielded a more precise picture of the topographic and functional anatomy of the pelvic floor in vivo and provided a basis for standardized image interpretation [Invanov et al, 1992;Christensen et al, 1995;Klutke and Siegel, 1995;Strohbehn et al, 1996a]. Numerous reports were published on the analysis and limits of dynamic MRI [Yang et al, 1991;Ozasa et al, 1992;Ghoniem et al, 1992;Goodrich et al, 1993;Ivanov et al, 1993;Fielding et al, 1996;Healy et al, 1997].…”
Section: Introductionmentioning
confidence: 99%